(untitled) (Revista Sistemas de Producción Agroecológicos, 2011)
The ostriches breeding is one of the new alternatives productive present in Colombia (South America), since 2004; nevertheless, there are scarce the local antecedents on the handling in captivity and they lack studies about the parasitic illnesses that these birds can suffer under the conditions of the eastern Plains of Colombia. Starting from that situation, two students of Degree in Agricultural Production and a Veterinary Medical professor into Eastern plains University, designed and they executed an investigation work, using animals of a farm located on the twelve (12) kilometer of the road that of the municipality of “Puerto López”, going to the municipality of "Puerto Gaitán”, on Meta Department, where it is the veredal zone "Alto navajas", there the property “El desquite” is located, and into it, the “Latin American” zoo farm. There they integrated by groups of different ages, for the taking and later technical process in the laboratory, of samples of blood, skin and fecal matter, to looking for parasites. Four (4) samplings were made with intervals of 45 days between them. Four (4) genres of parasitic were detected; of those which three (3) are the well-known internal parasites as Ascaridia galli, Entamoeba sp and Libyostrongylus sp. Too an external parasite called Strupthiopterolichus sculpturatus were identified, the feathers acarus.